2010
DOI: 10.1007/s00249-010-0650-7
|View full text |Cite
|
Sign up to set email alerts
|

Direct imaging of salt effects on lipid bilayer ordering at sub-molecular resolution

Abstract: The interactions of salts with lipid bilayers are known to alter the properties of membranes and therefore influence their structure and dynamics. Sodium and calcium cations penetrate deeply into the headgroup region and bind to the lipids, whereas potassium ions only loosely associate with lipid molecules and mostly remain outside of the headgroup region. We investigated a dipalmitoylphosphatidylcholine (DPPC) bilayer in the gel phase in the presence of all three cations with a concentration of Ca²+ ions an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 44 publications
5
24
0
Order By: Relevance
“…47 The binding of cations has a significant impact on the structural and dynamical properties of PC membranes. 45,48 A decrease of area per lipid and lipid lateral diffusion coefficient as an increase of salt concentration had been shown in MD simulations 45,48,53 in agreement with the decrease of the angle between the P−N 54 did not find a significant change in area per lipid, though tilting of the lipids' head groups out of the membrane plane was noted.…”
Section: ■ Introductionsupporting
confidence: 57%
“…47 The binding of cations has a significant impact on the structural and dynamical properties of PC membranes. 45,48 A decrease of area per lipid and lipid lateral diffusion coefficient as an increase of salt concentration had been shown in MD simulations 45,48,53 in agreement with the decrease of the angle between the P−N 54 did not find a significant change in area per lipid, though tilting of the lipids' head groups out of the membrane plane was noted.…”
Section: ■ Introductionsupporting
confidence: 57%
“…Molecular Dynamic simulations of the effects of monovalent ions on phospholipid bilayers revealed that the effect of the ions on the structure of the bilayer depends on the tendency of specific headgroups to form both intraand extra-molecular hydrogen bonds and on the specific ion at issue (Gurtovenko and Vattulainen, 2008). However, it should be noted that, in some cases, results from MD simulations and corresponding experimental data lack in consistency (Ferber et al, 2011). It is evident that the effect of ions should strongly depend on the overall charge in lipid headgroups, being strongest for more charged lipids.…”
Section: Overview Of the Force Spectroscopy Studies On Supported Lipimentioning
confidence: 90%
“…This conclusion has since been strengthened by further studies showing that bilayer properties remain unaltered upon the addition of sub-molar concentrations of monovalent salt 4,10,11 . Since 2000, however, another view has emerged, suggesting much stronger interactions between phospholipids and monovalent cations, and strong Na + binding in particular [6][7][8][9][12][13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%